Characterizing prevalence and ecological impact of non-native terrestrial isopods (Isopoda, Oniscidea) in tallgrass prairie - Singer, Caitlin; Bello, Nora M.; Snyder, Bruce A. (My University, 2013)
Isopods are terrestrial crustaceans whose role and impact in the tallgrass prairie ecosystem remains little explored despite being rather prevalent non-native inhabitants. To better understand this role, we conducted two related studies. The first was a rapid survey of isopods in experimental treatments at Konza Prairie LTER site to investigate the diversity and relative abundance of isopod species present. Of the four species known in Kansas thus far, all non-native, Armadillidium vulgare was the most abundantly found, accounting for 93% of individuals found. Armadillidium nasatum, Cylisticus convexus, and Porcellionides pruinosus were also found and we report the first record of Porcellio laevis in the State of Kansas. Survey results showed no evidence for a relationship between isopod abundance and fire frequency or grazing treatment. The second experiment was a food preference study to explore granivory in non-native isopods and characterize their seed predator behavior on native plants. Individual isopods were placed in Petri dishes with food options including leaf litter and seeds from one of 15 species; dishes were then incubated for 6-12 days and preference was assessed based on pre- and post-trial weights of the feed and individual isopod. Isopods showed a significant preference for leaves compared to seeds in nine of the 15 seed species evaluated; no evidence for leaf-vs.-seed preference was apparent in the remaining six seed species. However, in all cases, isopods did consume some amount of seeds even when leaf litter was present. Taken together, the relatively low abundance of non-native terrestrial isopods and their lack of apparent preference for native plant seeds suggest that isopods are unlikely to pose considerable threat to tallgrass prairie ecosystems. More extensive research, including a preference study with greater representation of seed species and a quantitative survey throughout the year, would be needed to further characterize the ecological role of isopods in the tallgrass prairie.
Keywords: Isopods; Crustaceans; Tallgrass prairie; Konza Prairie; Granivory